The Development of the Entrepreneurship Ecosystem and Digital Technology in Vocational Education - M. Syaom Barliana,; Sultono,; Tutin Aryanti,; Dedy Suryadi, (Journal of Technical Education and Training, 2025)
This study examines the development of the entrepreneurship ecosystem and the integration of digital technology in vocational education, with a specific focus on public vocational schools in West Java Province, Indonesia. The analysis is based on two main frameworks: the entrepreneurship ecosystem, comprising actor-related and factor-related elements, and the digital technology ecosystem, which encompasses aspects of hardware, software, and brainwaves. The research employs a cross-sectional survey method within a quantitative descriptive evaluation design. The sample comprises vocational school teachers and students selected using Slovin’s formula to ensure proportional representation. Data were collected using a validated and reliable structured questionnaire. The results were analyzed using frequency distribution and the Respondent Achievement Level (RAL) approach. The findings reveal significant variability across schools and indicators. Several digital technology indicators, such as the availability of free internet and the completeness of extracurricular entrepreneurship facilities, scored below 50%, indicating major areas for improvement. In contrast, indicators reflecting an entrepreneurial mindset and behavior, such as resilience, talent, and leadership, scored above 80%, demonstrating strong internal readiness for entrepreneurship development. The study highlights the need for targeted interventions in underperforming schools and continuous enhancement in schools already excelling. Inter-school collaboration is recommended, where high-performing schools can serve as best practice models to uplift others. These findings contribute valuable insights for vocational education stakeholders and policymakers, particularly in formulating strategies to enhance entrepreneurship education and foster digital-technology-based entrepreneurial competencies among students. Ultimately, the research supports the development of more adaptive and innovative vocational education ecosystems.